2005
DOI: 10.2144/05386st03
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Luciferase Assay System: One-Step Monitoring of Multiple Gene Expressions with a Single Substrate

Abstract: Reporter assays that use luciferase are widely employed for monitoring cellular events associated with gene expression. In general, firefly luciferase and Renilla luciferase are used for monitoring single gene expression. However, the expression of more than one gene cannot be monitored simultaneously by this system because one of the two reporting luciferases must be used as an internal control. We have developed a novel reporter assay system in which three luciferases that emit green, orange, and red light w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 12 publications
2
73
0
Order By: Relevance
“…BLI has been further applied to the in vivo study for simultaneous monitoring of multiple cellular events. Nakajima et al [56] developed a novel reporter assay system that emits three different colors (green, orange, and red light) using a single substrate. They demonstrated that this system enabled direct comparison of two or more transcriptional activities and/or interactions with transcription factors in the same cell population in a one-step reaction with a single luciferin.…”
Section: Imaging Of Bioluminescencementioning
confidence: 99%
“…BLI has been further applied to the in vivo study for simultaneous monitoring of multiple cellular events. Nakajima et al [56] developed a novel reporter assay system that emits three different colors (green, orange, and red light) using a single substrate. They demonstrated that this system enabled direct comparison of two or more transcriptional activities and/or interactions with transcription factors in the same cell population in a one-step reaction with a single luciferin.…”
Section: Imaging Of Bioluminescencementioning
confidence: 99%
“…10 The bioluminescent spectra of WT and mutant luciferases from transfected NIH3T3 cell extracts were evaluated. All mutants showed the similar spectral shape as WT; three (I212L, S463R, and I212L/S463R) had the same emission maximum as WT (kmax ca.…”
Section: Bioluminescent Emission Spectra Of Mutant Luciferasesmentioning
confidence: 99%
“…10,11 The optimized cDNA in mammalian expression vector (pCMV-SLR), whose expression is driven by the CMV promoter, was used as the template for mutation. Site-directed mutagenesis was performed using a KOD-Plus-Mutagenesis Kit (Toyobo) according to the manufacturer's instructions.…”
Section: Site-directed Mutagenesis and Screening For Mutantsmentioning
confidence: 99%
See 2 more Smart Citations